The Types of Code-Mixing Found in Maudy Ayunda’s YouTube Video in 2022 - Safina Amalia Bahri; Faisal (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
In the age of globalization, the absorption of foreign words into young people’s languages is frequently linked to the influence of many cultures, entertainment, lifestyles, information, and international business exchanges in modern society. This phenomenon is popular among young Indonesians who want to improve their social standing by increasing their education, modernism, aesthetic appeal, style, and elite status. Code mixing is one way to classify this occurrence. Code mixing occurs on all social media platforms frequented by young people, particularly YouTube. Based on Musyken’s theory, this study examines the many types of code mixing in Maudy Ayunda’s YouTube video in 2022. This study employed a descriptive qualitative approach. This study collected data using observation, content analysis, and note-taking techniques. The research’s results state that Maudy Ayunda used 54 instances of code-mixing utterances in the studied video. The most predominant type of code-mixing in the video is insertion with 25 instances while the most infrequent type of code-mixing in the video is alternation with 8 instances.